2016
DOI: 10.1534/genetics.115.186502
|View full text |Cite
|
Sign up to set email alerts
|

Powerful and Adaptive Testing for Multi-trait and Multi-SNP Associations with GWAS and Sequencing Data

Abstract: Testing for genetic association with multiple traits has become increasingly important, not only because of its potential to boost statistical power, but also for its direct relevance to applications. For example, there is accumulating evidence showing that some complex neurodegenerative and psychiatric diseases like Alzheimer's disease are due to disrupted brain networks, for which it would be natural to identify genetic variants associated with a disrupted brain network, represented as a set of multiple trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 55 publications
0
48
0
Order By: Relevance
“…Furthermore, the daSPU test identified 44 and 63 significant genes with a common set of 37 genes in the two analyses. Hence, in spite of the relatively small sample sizes and some differences between the two ADNI cohorts (Kim et al 2016), the two analyses yielded largely overlapping sets of the significant genes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the daSPU test identified 44 and 63 significant genes with a common set of 37 genes in the two analyses. Hence, in spite of the relatively small sample sizes and some differences between the two ADNI cohorts (Kim et al 2016), the two analyses yielded largely overlapping sets of the significant genes.…”
Section: Resultsmentioning
confidence: 99%
“…by weighting) the SNPs and endophenotypes will largely determine the statistical power of the test. The situation is similar to pathway-based association testing, which critically depends on the unknown association patterns of both the genes (in a pathway) and SNPs (in each gene) (Pan et al 2015), and to gene-based association testing on multiple traits, for which one has to account for possibly varying association patterns of the SNPs across the traits (Kim et al 2016). Accordingly, to maintain high statistical power with various unknown association patterns, as in the above previous works, we use two non-negative integers, γ 1 and γ 2 , to control the degrees of weighting over the SNPs and over the endophenotypes respectively, and the two parameters will be chosen data-adaptively as to be shown later.…”
Section: Methodsmentioning
confidence: 99%
“…Due to a relatively small sample size and usually small genetic effect sizes, applying a univariate test to the ADNI data failed to identify any SNP passing the genome-wide significance level at 5 × 10 −8 (Kim et al, 2016), and even a much larger meta-analysis of 74,046 individuals only identified very few genome-wide significant SNPs (Lambert et al, 2013). Hence, it is natural to consider possible associations at the pathway or even chromosome level, which may be more powerful through effect aggregation and a reduced burden of multiple testing, and shed light on the underlying genetic architecture.…”
Section: Real Data Analysismentioning
confidence: 99%
“…Most of these approaches assume a very specific and restricted Gaussian dependence structure between traits while there exist many empirical data sets with non-Gaussian dependencies. There exist some empirical comparisons of multivariate tests for the analysis of common (Kim et al, 2016;Liang et al, 2016;Zhu, Zhang, & Sha, 2015) and rare genetic variants (Broadaway et al, 2016;Dutta et al, 2019;B. Most of the above tests are multi-marker and "multivariate" tests (i.e., testing the association of all variants in a region with all traits jointly), hence they may not have optimal power for testing variants with large effect sizes and when the tested variants are only associated with a few of the tested traits.…”
Section: Introductionmentioning
confidence: 99%